A Construction Method of (2, 3) Visual Cryptography Scheme - Peng Li; Jianfeng Ma; Liping Yin; Quan Ma (IEEE Access)
Visual cryptography scheme (VCS) shares a binary secret image into multiple shadows, stacking qualified set of shadows will decode the secret image without computer resources. In this paper, we propose a (2, 3)-VCS, which can share one or two secret images into 3 shadows, stacking any two shadows will reveal the secret image. The shadow size is 3/2 times of the secret image. The contrasts of the revealed image are 1/3 and 1/2 when we share one and two secret images, respectively. We can also reveal the secret image by XOR decoding operation, and the visual quality of the revealed image can be further improved. By XOR decoding operation, the contrasts of the revealed image will be 2/3 and 1 when we share one or two secret images, respectively. In the case of sharing two secret images, the revealed two secret images have no distortion. Theoretic analysis and experimental results demonstrate the feasibility and advantages of the proposed (2, 3)-VCS.